SYNTHESIS OF FINANCIAL TECHNOLOGY AT PT JNE: TANSFORMASI LOGISTICS SERVICES INTO THE DIGITAL ERA - Vannessa Efendi; Ahmad Azmi (RADJA PUBLIKA, 2024)
This journal explores the transformative journey of PT JNE, a logistics service provider, as it embraces Financial Technology (FinTech) to adapt and thrive in the digital age. The synthesis encompasses the integration of innovative financial technologies within PT JNE's operations, shedding light on the impact, challenges, and opportunities encountered in this transition.